2008
DOI: 10.1016/j.virol.2007.09.003
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/AKT inhibition induces caspase-dependent apoptosis in HTLV-1-transformed cells

Abstract: The phosphatidylinositol-3-kinase (PI3K) and AKT (protein kinase B) signaling pathways play an important role in regulating cell cycle progression and cell survival. In previous studies, we demonstrated that AKT is activated in HTLV-1-transformed cells and that Tax activation of AKT is linked to p53 inhibition and cell survival. In the present study, we extend these observations to identify regulatory pathways affected by AKT in HTLV-1-transformed cells. We demonstrate that inhibition of AKT reduces the level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 55 publications
5
79
0
Order By: Relevance
“…[52][53][54] In our study Nutlin-3a caused rapid apoptosis in a number of ATL-related cell lines with wild-type p53, and typical targets of p53, such as BAX, NOXA, PUMA, DR5 and survivin, actually responded to Nutlin-3a treatment. These results indicate that Nutlin-3a can overcome Tax-induced p53 impairment even in cells with high Tax expression.…”
Section: Discussionmentioning
confidence: 54%
“…[52][53][54] In our study Nutlin-3a caused rapid apoptosis in a number of ATL-related cell lines with wild-type p53, and typical targets of p53, such as BAX, NOXA, PUMA, DR5 and survivin, actually responded to Nutlin-3a treatment. These results indicate that Nutlin-3a can overcome Tax-induced p53 impairment even in cells with high Tax expression.…”
Section: Discussionmentioning
confidence: 54%
“…Tumorigenesis is mainly due to checkpoint errors at G 1 /S and G 2 /M phases, allowing cells to become cancerous and proliferate malignantly. Treatment with a selective inhibitor such as LY294002 acting on the PI3k signalling pathway can cause some cells to arrest at G 1 phase [15,16], for example C81, MT-2, HUT102, but other cells arrest at G 2 /M phase, for example HEK293 [17,18]. Interestingly, our data showed that LY294002 could strongly block the cell cycle at each phase rather than just causing arrest at a specific phase, unlike the negative or positive controls It is known that cyclins play an important role in cellcycle regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Tax1 induces the phosphorylation of Akt that is linked to NF-B activation and p53 inhibition (Jeong et al, 2005). Inhibition of PI3K or Akt induces cell cycle arrest and apoptosis with accumulation of p27 Kip1 and caspase-9 activation in HTLV-1 transformed T-cells (Jeong et al, 2008). In addition, Tax1 down-regulates transcription for PTEN and SHIP-1 through NF-B-mediated inhibition of the transcriptional coactivator p300 (Fukuda et al, 2009).…”
Section: Intracellular Signalingmentioning
confidence: 99%